Functional outcomes associated with varying levels of targeted temperature management after out-of-hospital cardiac arrest — An INTCAR2 registry analysis. (1st January 2020) - Johnsson, Jesper; Wahlström, Josefine; Dankiewicz, Josef; Annborn, Martin; Agarwal, Sachin; Dupont, Allison; Forsberg, Sune; Friberg, Hans; Hand, Robert; Hirsch, Karen G.; May, Teresa; McPherson, John A.; et al.
Abstract: Introduction: Targeted temperature management (TTM) after out-of-hospital cardiac arrest (OHCA) has been recommended in international guidelines since 2005. The TTM-trial published in 2013 showed no difference in survival or neurological outcome for patients randomised to 33 °C or 36 °C, and many hospitals have changed practice. The optimal utilization of TTM is still debated. This study aimed to analyse if a difference in temperature goal was associated with outcome in an unselected international registry population. Methods: This is a retrospective observational study based on a prospective registry — the International Cardiac Arrest Registry 2. Patients were categorized as receiving TTM in the lower range at 32–34 °C (TTM-low) or at 35–37 °C (TTM-high). Primary outcome was good functional status defined as cerebral performance category (CPC) of 1–2 at hospital discharge and secondary outcome was adverse events related to TTM. A logistic regression model was created to evaluate the independent effect of temperature by correcting for clinical and demographic factors associated with outcome. Results: Of 1710 patients included, 1242 (72, 6%) received TTM-low and 468 (27, 4%) TTM-high. In patients receiving TTM-low, 31.3% survived with good outcome compared to 28.8% in the TTM-high group. There was no significant association between temperature and outcome ( p = 0.352). In analyses adjusted for baseline differences the OR for a good outcome with TTM-low was 1.27, 95% CI (0.94–1.73). Haemodynamic instability leading to discontinuation of TTM was more common in TTM-low. Conclusions: No significant difference in functional outcome at hospital discharge was found in patients receiving lower- versus higher targeted temperature management.